COMPUTER-AIDED INSTRUCTION TOOLS FOR ARCHITECTURE: CASE STUDY OF SINAN MOSQUES - Yazar, Tugrul; Colakoglu, Birgul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2007)
This paper introduces an ongoing research about the Computer Aided Instruction (CAI) tool which is based on the master thesis of Tugrul Yazar from Yildiz Technical University (YTU) Faculty of Architecture Computational Design Graduate Program (BOM). The thesis is named Expert Systems for Architectural Education: The Expert System of Sinan Mosques and completed in 2003 under the supervision of Dr. Birgul olakoglu. YTU Department of Computer Engineering supported this research by assigning the graduation project (student: Ali Murat Akkan) as programming the prototype software. The educational tool developed in this research aims to teach Sinan's mosque architecture by visualizing hypothetical mosque designs.
Keywords: Computer-aided instruction (CAI); architectural education; expert systems; Sinan; Architecture